2005
DOI: 10.1007/s11175-005-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electrochemical Noise of the Lithium Electrode in Aprotic Organic Electrolytes

Abstract: Processes that occur on the lithium electrode under open-circuit conditions and when polarized cathodically and anodically are studied by means of the electrochemical-noise method. The study is carried out in such aprotic organic electrolytes as 1 M solution of LiClO 4 in 1,3-dioxolane; 1 M solution of LiPF 6 in a mixture of ethylene carbonate and diethyl carbonate; and 1 M solution of LiN(CF 3 SO 2 ) 2 in 1,3-dioxolane. An analysis of the noise characteristics of the polarized electrode confirms that the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Thus, if the stationary corrosion transforms into the nonstationary one, i.e., if we have to do with the corrosion localization (the pitting formation), it can be identified by the method of the "noises" record, using certain techniques and special equipment and apparatuses [1]. The above method of electrochemical noises can also be used for the diagnosis of organic electrolytes of accumulators with a metal lithium electrode [5], as well as to determine the degree of a source discharge. V. A. Tyagai found that a slow discharge, fluctuations of reagents in the near-cathode region, the rate of a chemical reaction, photoexitation, intensive gas release (hydrogen, oxygen) on the electrodes, circuit resistance, etc., can be the sources of fluctuations in the electrical circuit rectifier-bath.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the stationary corrosion transforms into the nonstationary one, i.e., if we have to do with the corrosion localization (the pitting formation), it can be identified by the method of the "noises" record, using certain techniques and special equipment and apparatuses [1]. The above method of electrochemical noises can also be used for the diagnosis of organic electrolytes of accumulators with a metal lithium electrode [5], as well as to determine the degree of a source discharge. V. A. Tyagai found that a slow discharge, fluctuations of reagents in the near-cathode region, the rate of a chemical reaction, photoexitation, intensive gas release (hydrogen, oxygen) on the electrodes, circuit resistance, etc., can be the sources of fluctuations in the electrical circuit rectifier-bath.…”
Section: Introductionmentioning
confidence: 99%
“…Noise measurements have been widely used not only in the 1960s in relation to communication systems [7] and semiconductors [8] but also from time to time in electrochemical studies [9][10][11][12]. Electrochemical noise can be caused by different phenomena such as turbulent mass transfer [13][14][15][16][17], gas evolution [18][19][20], electrode corrosion [21][22][23][24] and passivation [25], or water transfer in fuel cells [26].…”
Section: Introductionmentioning
confidence: 99%